Analysis of Differentially Expressed MicroRNAs in OVA-induced Airway Remodeling Model Mice - Chang Xu; Yilan Song; Chongyang Wang; Jingzhi Jiang; Zhiguang Wang; Liangchang Li; Guanghai Yan (Iranian Journal of Allergy, Asthma and Immunology, 2022)
MicroRNAs (miRNAs) can participate in airway remodeling by regulating immune molecule expression. Here, we aimed to identify the differential miRNAs involved in airway remodeling. Airway remodeling was induced by ovalbumin in female BALB/C mice. The differentially expressed miRNAs were screened with microarray. GO (Gene Ontology) and KEGG enrichment analysis was performed. The miRNA target gene network and miRNA target pathway network were constructed. Verification with real-time PCR and Western blot was performed. We identified 63 differentially expressed miRNAs (50 up-regulated and 13 down-regulated) in the lungs of ovalbumin-induced airway remodeling mice. Real-time PCR confirmed that 3 miRNAs (mmu-miR-1931, mmu-miR-712-5p, and mmu-miR-770-5p) were significantly up-regulated, and 4 miRNAs (mmu-miR-128-3p, mmu-miR-182-5p, mmu-miR-130b-3p, and mmu-miR-20b-5p) were significantly down-regulated. The miRNA target gene network analysis identified key mRNAs in the airway remodeling, such as Tnrc6b (trinucleotide repeat containing adaptor 6B), Sesn3 (sestrin 3), Baz2a (bromodomain adjacent to zinc finger domain 2a), and Cux1 (cut like homeobox 1). The miRNA target pathway network showed that the signal pathways such as MAPK (mitogen-activated protein kinase), PI3K/Akt (phosphoinositide 3-Kinase/protein kinase B), p53 (protein 53), and mTOR (mammalian target of rapamycin) were closely related to airway remodeling in asthma. Collectively, differential miRNAs involved in airway remodeling (such as mmu-miR-1931, mmu-miR-712-5p, mmu-miR-770-5p, mmu-miR-128-3p mmu-miR-182-5p, and mmu-miR-130b-3p) as well as their target genes (such as Tnrc6b, Sesn3, Baz2a, and Cux1) and pathways (such as MAPK, PI3K/Akt, p53, mTOR pathways) have been identified. Our findings may help to further understand the pathogenesis of airway remodeling.